Service quality of a university foodservice expectations and experiences of students Josephine R. Ignacio-Cosino ; Lorraine F. Villanueva, advise. - Cosino, Josephine R. Ignacio (2006)
The study aimed to establish the expectations and experiences of students regarding the service quality of a university foodservice. A pre-tested survey questionnaire, adapted from the SERVQUAL instrument, was used to measure service quality using the five dimensions of tangibles, reliability, responsiveness, assurance and empathy. Wilconxon Signed Ranks Test and Principal Component Analysis were used in data analysis. Two focus group discussion were also conducted to augment the findings of the survey. The results showed that majority of the respondents were female, second year students from the College of Arts and Sciences who live either in a campus dormitory or in their own house outside the university area. They have a weekly allowance of P451 to P600. Most of them eat at fast food establishments outside campus while some patronize other canteens within campus. Lunch is the usual meal eaten at the university food service with friends as the usual companion. In terms of service quality expectations, the respondents have the highest expectations in the assurance dimension followed closely by tangibles. The lowest expectations is in the empathy dimension. In terms of actual experiences, the respondents rated the reliability dimension the highest, while empathy was rated the lowest. Using Wilconxon Signed Rank Test, the greatest gap is in the assurance dimension. Since the service quality problem of the university food service is in the tangibles dimension, which has the greatest gap between expectations and experiences, improvement in this area is viewed positively, though not seen as a priority by students, based on the focus group discussions. Principal Component Analysis was done to determine the importance of the five service quality dimensions. It was found out that the tangibles dimension is not significantly different from assurance and reliability. Thus, they are considered equally important. Furthermore, they are more important than responsiveness and empathy. It was also established that the five dimensions could be reduced to two in the setting studied-the combinations of "tangibles-empathy" and "reliability-assurance" dimensions. In addressing the service quality problems of the university food service, it was suggested that implementing marketing activities could be a relevant endeavor. Recommendation were given to address the service quality problems using the 7Ps of service marketing as point of reference. Consideration of nutrition as a unique service quality attribute in a university food service setting was also emphasized. Similar studies on other local food service establishments were recommended to further test the validity of the instrument used. The use of focus group discussion to augment survey results was also considered a valuable approach. Lastly, service quality studies can also be done for other support units of a university like the library, registrar,health service and student housing since in the university setting, students are and should be treated as customers.